(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2021)
This paper examines the use of television as a marketing tool. The impact of television on theadvertising business in the media, as well as the history of television and advertising. The paperexamines the pros and disadvantages of television advertisement from both an industrial and scholarlystandpoint. The paper’s conclusion section includes some predictions regarding the future of televisionadvertising. It emphasises that, despite technological advancements, television advertising will remain apowerful medium. The screens will never cease, and with television’s digitalization, advertising willcontinue to exist in this medium, but in a different shape and structure.